Leben auf dem Missionsfeld Chrischona-Pilgermissionare in Äthiopien (1856–1868) - Strebel, Barbara (Aethiopica, 2001)
The Crischona-missionaries encountered considerable difficulties in Ethiopia: slow communication with Europe, financial problems, complex processes of adaptation to or differentiation from Ethiopian culture and the missionary efforts within the Ethiopian Church. Ultimately, their enterprise was doomed to failure.